USABILITY ANALYSIS IN PAASAAR.COM APPLICATION USING THE SYSTEM USABILITY SCALE (SUS) APPROACH - Mohamad Rifqy Roosdhani; Jati Widagdo; Erika Ayu Amelia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The development of internet use in Indonesia to do online shopping continues to show an increase. Usability and accessibility are core human concepts computer interaction (HCI). These concepts are intended to ensure effectiveness and satisfaction of the system to users. Usability is considered throughout the standard. It states that all interactive products will have a user interface, and the quality of the user interface can have significant effect on the achievement of user goals. Paasaar.com application is an e-commerce platform that can be accessed through a website which is addressed at paasaar.com. This research method is descriptive quantitative. Data collection is done by method of answering the questionnaire that has been standard used for the SUS method. Questionnaire distributed to 100 people respondents to fill directly questionnaires were selected randomly. By calculation using the SUS formula, it is obtained as shown in Table 1. Based on Table 1, the value of 83.88 is obtained. This value means that it is in the Good category. Good in this case is in terms of system usability. So that the e-commerce developed is in accordance with user expectations and is feasible to be used and accessed more widely.